International review of cell and molecular biology. - Jeon, Kwang W. (Academic Press, 2010)
International Review of Cell and Molecular Biology presents current advances and comprehensive reviews in cell biology--both plant and animal. Articles address structure and control of gene expression, nucleocytoplasmic interactions, control of cell development and differentiation, and cell transformation and growth. Impact factor for 2008: 4.935. * Authored by some of the foremost scientists in the field * Provides up-to-date information and directions for future research * Valuable reference material for advanced undergraduates, graduate students and professional scientists.